(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the concepts of "tradition", "imitation" and "creative succession" in Turkish literary translation are scientifically and theoretically analyzed. "Tradition" in the sense of a complex of principles, methods and styles used by translators to translate literary works into another language, and "imitation" and "repeatability" in literary translation, which are interpreted as "re-creating the features of a work that already existed, following this or that artist in creative practice" the territory and boundaries of succession events are defined.